Etiology and Pathogenesis of Postoperative Cognitive Dysfunction (Review) - M. I. Neimark; V. V. Shmelev; A. A. Rakhmonov; Z. A. Titova (Общая реаниматология)
Impairment of higher mental functions can complicate the course of the postoperative period even after short and minimally invasive, including laparoscopic, surgical procedures. Postoperative cognitive dysfunction significantly challenges patients’ quality of life, negating real success of surgical intervention and anesthetic support. In some cases, early postoperative cognitive dysfunction may be one of the main predictors of persistent cognitive impairment.The purpose of the review. To contemplate etiology, pathogenesis and the current perspective of postoperative cognitive dysfunction.We analyzed 96 publications in various databases (PubMed, Medline, RSCI and others), including 67 papers published over the past 5 years.The review provides an overview of current definitions and classification of postoperative cognitive dysfunction, data on the prevalence, polyethyology and risk factors, potential impact of the type of anesthesia and surgical intervention on the development of postoperative cognitive dysfunction. Various pathogenetic mechanisms of higher mental functions impairment alongside with available effective pharmacotherapies to correct them were considered.Conclusion. Numerous adverse factors of the perioperative period, such as neurotoxic effects of general anesthetics, neuroinflammation in response to operational stress and surgical trauma, impaired autoregulation of the cerebral blood flow, imperfect oxygen homeostasis, interactions of neurotransmitter, etc., can potentially cause postoperative cognitive dysfunction. Further deeper insights into etiology and pathogenesis of early postoperative cognitive dysfunction are relevant and necessary to improve prevention strategies and identify most effective pharmacotherapies to correct such disorders.